Persepsi Masyarakat dalam Membayar Zakat di BAZNAS Kabupaten Pasaman Barat - Yarham, M.; Siregar, Saima Putri (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2021)
This study aims to determine people's perceptions in paying zakat in BAZNAS, West Pasaman Regency where people still pay zakat according to the traditions in the area. This type of research is a qualitative descriptive study, using a phenomenological approach. Methods of data collection through observation, interviews, documentation. The results of this study indicate that there are still many people who do not know and understand the importance of the function, purpose and benefits of zakat in the payment or distribution of zakat through the Amil Zakat Institute in BAZNAS, West Pasaman Regency. Most people think that giving zakat directly to people in need is more affordable than BAZNAS. Then, because the community still lacks confidence and is not sure of the responsibility of an institution in handling zakat management and the ineffective existence of zakat collection units (UPZ) in the area. Keywords: Perception, Zakat, BAZNAS